Management of Uveitic Glaucoma in Children with Blau syndrome - Ivone Caroline; Elsa Gustianty; Andika Prahasta; R. Maula Rifada (Majalah Oftalmologi Indonesia, 2022)
Introduction: Glaucoma in children is a condition that potentially cause blindness. Management of uveitic glaucoma is challenging because of the many mechanisms involved in its pathogenesis Purpose: To report clinical characteristic and management of uveitic glaucoma in children with Blau Syndrome. Methods: A 13 years old boy came to the hospital with chief complain blurred vision in both eyes. The patient was diagnosed as Blau Syndrome one year ago. He had history of trabeculectomy on his left eye. Scalling skin and swollen joints was found on physical examination. Visual acuity was hand movement in both eyes, intraocular pressure was 34 (right) and 40 (left). Gonioscopy of the right eye was schwabe line in superior and peripheral anterior synechia in three quadrants. At the left eye, there was scleral spur in all quadrant. At the anterior segment of right eye, there was band keratopathy, posterior synechia 360 o , peripheral anterior synechia, and cataract. While at the left eye, there was bleb, band keratopathy, posterior synechia, peripheral iridotomy, and cataract. Trabeculectomy, 5 fluorouracil, synechiolysis, iris retractor, and membranectomy was performed for the right eye. Conclusion: Uveitic glaucoma in children poses a significant risk of blindness and needs an aggressive treatment to control intraocular pressure and amblyopia therapy to preserve vision.